Daily Interpersonal Events in Pain Patients: Applying Action Theory to Chronic Illness - Davis, Mary C. (2006)
Action theory proposes that individuals actively shape and then respond to their environments, highlighting the role of stable person characteristics in the development and maintenance of life’s interpersonal difficulties. In this study, we adopted the action perspective in our examination of the daily lives of chronic pain patients with rheumatoid arthritis. Our evaluation of patients’ daily diary reports indicated that individuals played a more prominent role in shaping their positive versus their negative social worlds. The contribution of symptoms of ill health and demographic characteristics, as well as personality attributes were also examined as stable factors that predicted exposure to and appraisal of events. In addition to between-person measures, day to day variations in illness symptoms also played a key role in predicting their social experinces. Together, these findings suggest that stable person characteristics and within-person fluctuations in ill health are each tied to daily interpersonal experiences for those in chronic pain. More broadly, they point to the value of capturing the experiences of individuals intensively over time, an approach that can help to elaborate the contributions of both stable factors and circumstance in shaping our social contexts.